2018
DOI: 10.3389/fnins.2018.00342
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Quality Control in Neurodegenerative Diseases: Focus on Parkinson's Disease and Huntington's Disease

Abstract: In recent years, several important advances have been made in our understanding of the pathways that lead to cell dysfunction and death in Parkinson's disease (PD) and Huntington's disease (HD). Despite distinct clinical and pathological features, these two neurodegenerative diseases share critical processes, such as the presence of misfolded and/or aggregated proteins, oxidative stress, and mitochondrial anomalies. Even though the mitochondria are commonly regarded as the “powerhouses” of the cell, they are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(107 citation statements)
references
References 301 publications
(358 reference statements)
2
105
0
Order By: Relevance
“…In a transgenic mouse model of HD, they found that the structure of complex II was affected early in HD, and overexpressing complex II reduced the effects of mutated Htt on striatal neurons, relieving them from neuronal dysfunction. In other studies, this reduction in complex II was accompanied by a reduction in ATP production, as insufficient oxidative phosphorylation results in a disruption of mitochondrial metabolism …”
Section: Mitochondrial Dysfunction In Neurodegenerationmentioning
confidence: 76%
See 1 more Smart Citation
“…In a transgenic mouse model of HD, they found that the structure of complex II was affected early in HD, and overexpressing complex II reduced the effects of mutated Htt on striatal neurons, relieving them from neuronal dysfunction. In other studies, this reduction in complex II was accompanied by a reduction in ATP production, as insufficient oxidative phosphorylation results in a disruption of mitochondrial metabolism …”
Section: Mitochondrial Dysfunction In Neurodegenerationmentioning
confidence: 76%
“…In other studies, this reduction in complex II was accompanied by a reduction in ATP production, as insufficient oxidative phosphorylation results in a disruption of mitochondrial metabolism. 86,88 The effect of mutant Htt on mitochondrial dynamics has also become a key focus in HD research. HD patients were found to have an imbalance in mitochondrial dynamics proteins, in postmortem tissue taken from the striatum of HD patients.…”
Section: Huntington's Diseasementioning
confidence: 99%
“…As a critical component of axonal mitochondrial transport, Miro occupies a central role in regulating mitochondrial position and turnover, a process critical to the health of neurons . In this section, we will discuss the link between Miro and mitochondrial biology with neurodegeneration.…”
Section: Miro Regulation In Neurodegenerative Diseasementioning
confidence: 99%
“…Mitochondrial quality control pathways are essential to maintain their proper function and ensure overall cell health and survival. Dysfunction in these pathways is associated with several human pathologies, such as neurodegenerative disease and cardiomyopathy (Campos et al , ; Franco‐Iborra et al , ). Mitophagy, the autophagic degradation of damaged mitochondria (Lemasters, ), is one of the most well‐studied mechanisms of mitochondrial quality control and is an important pathway aimed at sequestering whole, damaged mitochondria to ensure their degradation in lysosomes.…”
Section: Introductionmentioning
confidence: 99%